Influence of circadian rhythms on television viewers' behaviour: is there a need for new programming?. Issue 1 (2nd January 2016) - Müller, Helge H.; Moeller, Sebastian; Ott, Benjamin; Maihöfner, Christian; Sperling, Wolfgang
Abstract : As a common activity, television (TV) watching plays an important role in leisure behaviour. The influence of circadian rhythms on nearly all aspects of leisure behaviour and social life has been well examined in many fields. Less is known about circadian influences on TV use/social behaviour, and inconsistent findings have been reported. We analysed epidemiologic data from public TV stations to interpret them in light of circadian/seasonal rhythms and their interaction with leisure behaviour with the goal of improving quality of life by using TV as a pure leisure activity. We found that TV programme schedules failed to synchronise with circadian rhythms. Problems with synchronisation were observed for all viewers and were significantly related to factors such as working behaviour and social activities. Future studies should focus on the circadian influence on TV watching as a leisure behaviour. We propose a newly defined schedule based on circadian influences.